Gait Training in Virtual Reality: Short-Term Effects of Different Virtual Manipulation Techniques in Parkinson’s Disease - Janeh, Omar (Cells, 2019)
It is well documented that there is a strong relationship between gait asymmetry and the freezing of gait (FOG) in Parkinson’s Disease. The purpose of this pilot study was to find a “virtual reality (VR)- based” gait manipulation strategy to improve gait symmetry by equalizing step length. Fifteen male PD patients (mean age of 67.6 years) with FOG were assessed on a GAITRite(®) walkway. Natural gait was compared with walking conditions during “VR-based” gait modulation tasks that aimed at equalizing gait symmetry using visual or proprioceptive signals. Compared to natural gait, VR manipulation tasks significantly increased step width and swing time variability for both body sides. Within the VR conditions, only the task with “proprioceptive-visual dissociation” by artificial backward shifting of the foot improved spatial asymmetry significantly with comparable step lengths of both sides. Specific, hypothesis-driven VR tasks represent an efficient tool to manipulate gait features as gait symmetry in PD potentially preventing FOG. This pilot study offers promising “VR-based” approaches for rehabilitative training strategies to achieve gait symmetry and prevent FOG.